Defense expenditure and economic growth: A case study of Pakistan - Haseeb, Muhammad (2014)
The objective of this study was to examine whether there is exists a long run relationship between defense expenditure and economic growth, and investigate the plausibility of using defense expenditure as a macroeconomic stabilization tool (referred as Military Keynesianism Hypothesis) in case of Pakistan over the period 1975–2010. The Autoregressive Distributed Lag (ARDL) bounds testing approach was used to find out long run relationship between defense expenditure, economic growth, development expenditure, inflation and national saving. The Augmented Dickey-Fuller (ADF) test was used for checking stationarity. The results of ADF test revealed that inflation and saving are stationary at level while defense expenditure, development expenditure and GDP become stationary at first difference. Results of ARDL indicated that data is stable and confirmed the existence of long run relationship. The robustness of the model has been confirmed by diagnostic tests for serial correlation, function form, normality, hetroscedasticity, and structural stability for the model. The selected model generally passes all diagnostic tests and proves the robustness of the selected model. Moreover, results show that defense expenditure has negative impact on economic growth while saving has positive impact on economic growth but other variables have no impact on economic growth. These results for long run negative relationship between defense expenditure and economic growth suggest that in case of Pakistan MKH does not hold over the estimation period. The negative long run relationship between defense expenditure and economic growth implies that the policy makers need to have a greater focus on development spending as compared to defense spending.